Use of Calcium Channel Blockers and Parkinson’s Disease - Pasternak, Björn; Svanström, Henrik; Nielsen, Nete M.; Fugger, Lars; Melbye, Mads; Hviid, Anders (American journal of epidemiology, 2012)
Experimental evidence and case-control studies suggest that dihydropyridine calcium channel blockers (DiCCBs) may protect against Parkinson's disease. The authors conducted a historical cohort study in Denmark to investigate the association between DiCCB use and risk of Parkinson's disease (1998-2006). Individual-level data on filled drug prescriptions, diagnostic information, and covariates were linked between nationwide registries. Among DiCCB users, 173 incident cases of Parkinson's disease were detected during 461,984 person-years of follow-up, compared with 5,538 cases during 17,343,641 person-years of follow-up among nonusers. After adjustment for age, sex, year, propensity score, and use of other antihypertensive drugs and statins, DiCCB use was associated with a reduced risk of Parkinson's disease (rate ratio (RR) = 0.71, 95% confidence interval (CI): 0.60, 0.82). This association was not present in patients who had previously used DiCCBs (RR = 1.04, 95% CI: 0.87, 1.24). DiCCB users aged ≥65 years were at lower risk of Parkinson's disease than DiCCB users aged <65 years (RR = 0.59, 95% CI: 0.40, 0.85). Among patients with Parkinson's disease, DiCCB use was associated with reduced risk of death (adjusted RR = 0.66, 95% CI: 0.47, 0.91) but not dementia (adjusted RR = 0.97, 95% CI: 0.60, 1.56). In conclusion, DiCCB exposure was associated with a reduced risk of incident Parkinson's disease, particularly in older patients, and with reduced mortality among patients with Parkinson's disease.